On resource sharing and careful overbooking for network virtualisation. (8th April 2011) - Fiedler, Markus
Network virtualisation implies the need for sharing network resources. However, exclusive resource allocation to users drives blocking probabilities and cost while potentially leaving precious resources underutilised in constrained environments. Motivated by these observations, this paper analyses careful overbooking according to Service Level Agreements that specify desired degrees of availability. Besides of full availability of the requested resources, a second level of limited availability, implying a well-defined reduction of the allocated resource, is taken into account. Particular attention is paid to the gain borderline, representing the possibility of accommodating one extra user beyond exclusive allocation without violating the SLAs. Simple but telling formulae provide insights into requirements for careful overbooking, worst-case capacity reduction factors from full to limited availability, and the conditions under which it is sensible to integrate users with different activity levels. We also link capacity reductions to potential decreases in quality of experience.